Prescriptions of antihypertensive drugs are influenced by the characteristics of general practitioners and their patients: a cross-sectional study in Normandy, France - Xavier HUMBERT; Andry Rabiaza (James Cook University, 2023)
Introduction: Hypertension is associated with significant cardio-vascular morbi-mortality. However, hypertension control is low, especially in France. The reasons influencing general practitioners’ (GPs) prescription of antihypertensive drugs (ADs) remains unclear. This study aimed at assessing the influence of GP and patient characteristics on AD prescriptions.Methods: A cross-sectional study based on a sample of 2165 GPs was realized in Normandy (France) in 2019. The ration of AD prescription to overall prescription volume was calculated for each GP and allowed the definition of a 'low or high AD prescriber'. Associations of this AD prescription ratio with GP’s age, gender, practice location, number of years of practice, number of consultations, number and age of registered patients, patients' income and number of patients with a chronic condition were assessed using univariate and multivariate analysis.Results: Low prescriber GPs were 51.3±11.2 years-old and were mainly women (56%). In the multivariate analysis, low prescribers were associated with urban practice (OR: 1.47, 95%CI: 1.14-1.88), GP’s younger age (OR: 1.87, 95%CI: 1.42-2.44), patient's younger age (OR: 3.39, 95%CI: 2.77-4.15), more patient consultations (OR: 1.33, 95%CI: 1.11-1.61), lower income patients (OR: 1.44, 95%CI: 1.17-1.76) and fewer diabetes mellitus patients (OR: 0.72, 95%CI: 0.59-0.88).Discussion: Prescriptions of ADs are influenced by the characteristics of GPs and their patients. In future work, a more detailed assessment of all components of the consultation (in particular home blood pressure monitoring use) is necessary to explain AD prescription in general practice.